PERUBAHAN PERSEPSI ALIH FUNGSI LAHAN OLEH MASYARAKAT AKIBAT PROYEK BANDARA INTERNASIONAL YOGYAKARTA - Poetri, Shafira Rizqi Aditya; Iskandar, Doddy Aditya (Jurusan Teknik Perencanaan Wilayah dan Kota, Fakultas Sains dan Teknologi, Universitas Islam Negeri Alauddin Makassar, 2024)
National Strategic Projects are developed to boost economic performance and ensure equitable development. One of these national strategic projects is Yogyakarta International Airport, located in Kulonprogo Regency. The Yogyakarta International Airport was constructed from 2018 to 2020 and began full operations in 2020. The presence of the airport has influenced the emergence of new economic activities and job opportunities. The response to these new opportunities and economic benefits has been the conversion of land to meet the market demand for land. This study aims to observe the community's response in relation to the stages of the Yogyakarta International Airport project. Each stage of development creates different opportunities and elicits different responses from the community. The decision to convert land is based on various types of land conversion. Using qualitative methods, this research seeks to explore the various perceptions of the community members who engage in land conversion. The results of the analysis reveal changes in community responses and opportunities depending on the ongoing process. The location of the land also plays a significant role in the diversity of how the community utilizes the land for conversion. The expected benefit of this study is to present the phenomena arising from the community's response to the existence of Yogyakarta International Airport, providing insights for the formulation and implementation of spatial planning policies.